1995
DOI: 10.1111/j.1365-2141.1995.tb03302.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation treatment for childhood virus‐associated haemophagocytic lymphohistiocytosis

Abstract: The Epstein-Barr virus (EBV), or human herpesvirus-6 (HHV-6) associated haemophagocytic lymphohistiocytosis, has been found prevalent in Taiwan; it affects previously healthy children and is always fatal when treated only supportively. Recognition of the underlying pathogenesis for this disease prompted adoption of an immunomodulatory regimen of intravenous immunoglobulin (IVIG) and/or etoposide on 17 such patients treated between 1990 and 1993. Remarkable improvement in patients' prognoses was demonstrated. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 25 publications
1
56
0
1
Order By: Relevance
“…14,15 In practice, allogeneic SCT might be required only when recurrent disease develops, since it is possible to control EBV-HLH in a high proportion of cases without resorting to SCT. 5,16 To our knowledge, this is the first case with EBV-HLH in which CBSCT was successfully performed. As previously reported for successful CBSCT for familial hemophagocytic lymphohistiocytosis (FEL) cases, 17,18 this approach has potential for control of HLH.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 In practice, allogeneic SCT might be required only when recurrent disease develops, since it is possible to control EBV-HLH in a high proportion of cases without resorting to SCT. 5,16 To our knowledge, this is the first case with EBV-HLH in which CBSCT was successfully performed. As previously reported for successful CBSCT for familial hemophagocytic lymphohistiocytosis (FEL) cases, 17,18 this approach has potential for control of HLH.…”
Section: Discussionmentioning
confidence: 99%
“…Success of intravenous immunoglobulin requires treatment early in the course of MAS. 82 Although often useful for the treatment of infection-triggered MAS 83,84 and a few children with sJIA, 72,85 children with MAS as part of sJIA are often refractory to intravenous immunoglobulin. 86 A more aggressive approach using anti-thymocyte globulin has been proposed for FHLH 87 and has been used successfully in two patients with probable MAS.…”
Section: Traditional Therapy For Mas In the Setting Of Sjiamentioning
confidence: 99%
“…4,5 Abughali et al 3 reported a case of congenital tuberculosis with the onset of fever at 3 days of age. The disease was not diagnosed until 2 weeks of life.…”
Section: Discussionmentioning
confidence: 99%
“…Successful treatment of IAHS usually depends on a specific treatment for the known infectious agent and adequate supportive care. Treatment with intravenous immunoglobulin has been reported to improve the outcome of virus-associated hemophagocytic syndrome, 5 but no information has been reported for the treatment of IAHS associated with tuberculosis. Our patient did not respond to treatment with intravenous immunoglobulin, and the resolution of IAHS seemed to be the result of an adequate treatment for tuberculosis.…”
Section: Discussionmentioning
confidence: 99%